Pancasila as The Basis of The State Unity of The Republic of Indonesia - Palmawati Taher (Pancasila and Law Review, 2021)
Indonesia is facing various challenges because some people do not use religious and cultural values as a source of ethics in the nation and state. Socio-cultural conflicts have occurred due to ethnic, cultural, and religious pluralism that the government and society are not appropriately managed and fair. Based on that, Pancasila is needed by all generations of the nation. The type of research method used in this research is normative research, namely research on library materials which are primary data in science is classified as secondary data, which relies on data collection tools in the form of library studies or document studies. The research concludes that generations need Pancasila to unify the nation. Even though the Indonesian people are now united, it does not mean that Pancasila is no longer needed. Because what is called the Indonesian nation is what is currently there and what will exist in the future. As long as the regeneration process continues, we still need Pancasila as a unifying nation.